Immigrants as victims: Examining the function of assimilation. Issue 2 (2nd April 2016) - Luo, Fei; Bouffard, Leana Allen
ABSTRACT: Research on victimization suggests that low self-control substantially increases the risk of victimization. Previous research has investigated the effect of low-self-control among a variety of samples. Seldom examined is the immigrant population. Because immigrants have become an important component of the U.S. population and are fast increasing in number, it is important to study their victimization experience. Immigrants possess different backgrounds and cultures, and they may have different levels of self-control and victimization experiences. In addition, immigrants undergo an assimilation process that may influence the association between self-control and victimization. Our results show that the association between low self-control and victimization is robust and valid among immigrants. Assimilation has an independent effect on victimization but does not influence this association.